Development and validation of a one-step SMN assay for genetic testing in spinal muscular atrophy via MALDI-TOF MS - Xing, Xiaodong; Ji, Xing; Liu, Xinzhu; Jin, Xiaohui; He, Zhenglei; Xu, Ajing; Jiang, Wengao; Ji, Wenbo; Liu, Yan; Zhang, Jian; Huang, Xiaohui (Analyst (London), 2024)
Spinal muscular atrophy (SMA) is a fatal neuromuscular disorder primarily attributed to the homozygous deletion of the survival motor neuron 1 ( SMN1 ) gene, with disease severity closely correlated to the copy number variations (CNV) of SMN2 . Conventional methodologies, however, fail to provide a comprehensive gene overview of SMN and are often both time-intensive and costly. In this study, we present a novel one-step MALDI-TOF MS assay for SMA gene testing. To accurately quantify CNV, we incorporated RPPH1 as an internal control alongside normal samples and competing templates targeting SMN1 , SMN2 , and RPPH1 for multiple corrections. The CNV assay enables precise quantification of exons 7/8 in both SMN1 and SMN2 genes, achieving a kappa value of 0.935 ( P < 0.001) when compared with multiple ligation-dependent probe amplification (MLPA) during its development phase. This accuracy was further corroborated in a cohort comprising 78 individuals. To identify patients harboring compound heterozygous mutations or silent carriers, prevalent pathogenic variants along with sequence variants of SMN1 were integrated into our analysis framework; plasmids were constructed for methodological validation purposes. Utilizing these combinatorial assays for SMN detection, we identified one patient exhibiting a compound heterozygous mutation characterized by genotype [0 + 1 d ] and another subject presenting genotype [2 + 1], who harbored simultaneous variants of g.27134T > G and g.27706_27707delAT. The CNV assessment combined with pathogenic variants analysis developed through MALDI-TOF MS provides a comprehensive gene profile of SMN within a single analytical run. Given its unparalleled cost-effectiveness and time efficiency, this approach holds significant promise for further application in clinical diagnosis as well as newborn screening for SMA.